Biogeochemical controls on dissolved micronutrient (Ni, Cu, Zn, Cd) distributions in the Equatorial Pacific Ocean - Naman D. Singh; Zvi Steiner; Rena Czeschel; Peter Brandt; Yuping Guo; Xue-Gang Chen; Jana Blanke; Angèle Nicolas; Jinqiang Guo; Kathleen J. Gosnell; Edel M. O’Sullivan; Dominik Jasinski; et al. (Geochimica et Cosmochimica Acta, 2026)

Benefits and challenges of pasture cropping: Perceptions of grazing producers in the United States - Tong Wang; Akinsola Oyebanji; Tim Steffens; Srinivasulu Ale; Bhupinder Singh; Miranda Stotz; Hardev Singh (Rangelands, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Methane sink function of grassland soil microbiomes - negative effects of intensive management persist three years after land-use extensification - Nils Volles; Hauke Winter; Verena Groß; Milos Bielcik; Tim Urich; Steffen Kolb; Sven Marhan (Soil Biology and Biochemistry, 2025)

Tectonic modulation of caldera volcanism on the South Aegean Volcanic Arc - Abigail Metcalfe; Tim Druitt; Katharina Pank; Steffen Kutterolf; Jonas Preine; Sarah Beethe; Axel Schmitt; Christian Hübscher; Paraskevi Nomikou; Thomas A. Ronge; Carole Berthod; Hehe Chen; et al. (Earth and Planetary Science Letters, 2025)

Dynamics of dissolved trace metals, rare earth elements and Pb isotopes across the eastern margins of the Mediterranean Sea - Tal Benaltabet; Gil Lapid; Ronen Alkalay; Yishai Weinstein; Tim Steffens; Eric P. Achterberg; Adi Torfstein (Marine Chemistry, 2025)

Techno-economic analysis of proton exchange membrane fuel cell recycling through pyro- and hydrometallurgy - Tim Kemperdick; Peter Letmathe; Thomas Brachmann; Steffen Jahn; Artur Poeppel (Journal of Cleaner Production, 2025)

Validation of GEMS operational v2.0 total column NO2 and HCHO during the GMAP/SIJAQ campaign - Kangho Bae; Chang-Keun Song; Michel Van Roozendael; Andreas Richter; Thomas Wagner; Alexis Merlaud; Gaia Pinardi; Martina M. Friedrich; Caroline Fayt; Ermioni Dimitropoulou; Kezia Lange; Tim Bösch; et al. (Science of The Total Environment, 2025)

Multi-amplicon nitrogen cycling gene standard: An innovative approach for quantifying N-transforming soil microbes in terrestrial ecosystems - Christopher J. Gillespie; Tim L. Sit; Althea J. Loucanides; Jialin Hu; Brooke E. Matusko; Nicholas R. Terwilliger; Wei Shi; Samantha M. Steffen; Alex L. Woodley; Shuijin Hu (Soil Biology and Biochemistry, 2024)

Truthful yet misleading: Consumer response to ‘low fat’ food with high sugar content - Steffen Jahn; Ossama Elshiewy; Tim Döring; Yasemin Boztug (Food Quality and Preference, 2023)

Characterization and differentiation of sublittoral sandbanks in the southeastern North Sea - Jan Beermann; Lars Gutow; Steffen Wührdemann; Rebecca Konijnenberg; Kathrin Heinicke; Tim Bildstein; Sandra Jaklin; Manuela Gusky; Michael L. Zettler; Jennifer Dannheim; Roland Pesch (Biodiversity and Conservation, 2023)
Marine sublittoral sandbanks are essential offshore feeding grounds for larger crustaceans, fish and seabirds. In the southern North Sea, sandbanks are characterized by considerable natural sediment dynamics and are subject to chronic bottom trawling. However, except for the Dogger Bank, sandbanks in the southeastern North Sea have been only poorly investigated until now. We used an extensive, multi-annual dataset covering ongoing national monitoring programmes, environmental impact assessments, and basic research studies to analyse benthic communities on sublittoral sandbanks, evaluating their ecological value against the backdrop of similar seafloor habitats in this region. The analysis revealed complex spatial structuring of sandy seafloor habitats of the southeastern North Sea. Different infauna clusters were identified and could be specified by their composition of characteristic species. The sandbanks shared common structural features in their infauna community composition although they were not necessarily characterized by particularly high biodiversity compared to other sandy habitats. A close association of one of the main bioturbators in the southern North Sea, the sea urchin Echinocardium cordatum , with sandbanks was detected, which may promote the sediment-bound biogeochemical activity in this particular seafloor habitat. This would corroborate the status of sandbanks as sites of high ecological value calling for consideration in marine conservation.

Grazing patterns, diet quality, and performance of cow-calf pairs using continuous or rotational grazing in the Texas panhandle USA - Larry D. Fritzler; Tim J. Steffens; Marty B. Rhoades; David G. Lust (Journal of Arid Environments, 2023)

Quantification of Fracture Roughness by Change Probabilities and Hurst Exponents - Tim Gutjahr; Sina Hale; Karsten Keller; Philipp Blum; Steffen Winter (Mathematical Geosciences, 2022)
The objective of the current study is to utilize an innovative method called “change probabilities” for describing fracture roughness. In order to detect and visualize anisotropy of rock joint surfaces, the roughness of one-dimensional profiles taken in different directions is quantified. The central quantifiers, change probabilities, are based on counting monotonic changes in discretizations of a profile. These probabilities, which usually vary with the scale, can be reinterpreted as scale-dependent Hurst exponents. For a large class of Gaussian stochastic processes, change probabilities are shown to be directly related to the classical Hurst exponent, which generalizes a relationship known for fractional Brownian motion. While related to this classical roughness measure, the proposed method is more generally applicable, therefore increasing the flexibility of modeling and investigating surface profiles. In particular, it allows a quick and efficient visualization and detection of roughness anisotropy and scale dependence of roughness.

Genetic testing and surveillance in infantile myofibromatosis: a report from the SIOPE Host Genome Working Group - Simone Hettmer; Guillaume Dachy; Guido Seitz; Abbas Agaimy; Catriona Duncan; Marjolijn Jongmans; Steffen Hirsch; Iris Kventsel; Uwe Kordes; Ronald R. de Krijger; Markus Metzler; Orli Michaeli; et al. (Familial Cancer, 2021)
Infantile myofibromatosis (IM), which is typically diagnosed in young children, comprises a wide clinical spectrum ranging from inconspicuous solitary soft tissue nodules to multiple disseminated tumors resulting in life-threatening complications. Familial IM follows an autosomal dominant mode of inheritance and is linked to PDGFRB germline variants. Somatic PDGFRB variants were also detected in solitary and multifocal IM lesions. PDGFRB variants associated with IM constitutively activate PDGFRB kinase activity in the absence of its ligand. Germline variants have lower activating capabilities than somatic variants and, thus, require a second cis-acting hit for full receptor activation. Typically, these mutant receptors remain sensitive to tyrosine kinase inhibitors such as imatinib. The SIOPE Host Genome Working Group, consisting of pediatric oncologists, clinical geneticists and scientists, met in January 2020 to discuss recommendations for genetic testing and surveillance for patients who are diagnosed with IM or have a family history of IM/ PDGFRB germline variants. This report provides a brief review of the clinical manifestations and genetics of IM and summarizes our interdisciplinary recommendations.

Inflammatory Responses of Astrocytes Are Independent from Lipocalin 2 - Natalie Gasterich; Sophie Wetz; Stefan Tillmann; Lena Fein; Anke Seifert; Alexander Slowik; Ralf Weiskirchen; Adib Zendedel; Andreas Ludwig; Steffen Koschmieder; Cordian Beyer; Tim Clarner (Journal of Molecular Neuroscience, 2021)

Divergent drivers of the microbial methane sink in temperate forest and grassland soils - Jana Täumer; Steffen Kolb; Runa S. Boeddinghaus; Haitao Wang; Ingo Schöning; Marion Schrumpf; Tim Urich; Sven Marhan (Global Change Biology, 2021)
Aerated topsoils are important sinks for atmospheric methane (CH 4 ) via oxidation by CH 4 ‐oxidizing bacteria (MOB). However, intensified management of grasslands and forests may reduce the CH 4 sink capacity of soils. We investigated the influence of grassland land‐use intensity (150 sites) and forest management type (149 sites) on potential atmospheric CH 4 oxidation rates (PMORs) and the abundance and diversity of MOB (with qPCR) in topsoils of three temperate regions in Germany. PMORs measurements in microcosms under defined conditions yielded approximately twice as much CH 4 oxidation in forest than in grassland soils. High land‐use intensity of grasslands had a negative effect on PMORs (−40%) in almost all regions and fertilization was the predominant factor of grassland land‐use intensity leading to PMOR reduction by 20%. In contrast, forest management did not affect PMORs in forest soils. Upland soil cluster (USC)‐α was the dominant group of MOBs in the forests. In contrast, USC‐γ was absent in more than half of the forest soils but present in almost all grassland soils. USC‐α abundance had a direct positive effect on PMOR in forest, while in grasslands USC‐α and USC‐γ abundance affected PMOR positively with a more pronounced contribution of USC‐γ than USC‐α. Soil bulk density negatively influenced PMOR in both forests and grasslands. We further found that the response of the PMORs to pH, soil texture, soil water holding capacity and organic carbon and nitrogen content differ between temperate forest and grassland soils. pH had no direct effects on PMOR, but indirect ones via the MOB abundances, showing a negative effect on USC‐α, and a positive on USC‐γ abundance. We conclude that reduction in grassland land‐use intensity and afforestation has the potential to increase the CH 4 sink function of soils and that different parameters determine the microbial methane sink in forest and grassland soils.

Fluid Flow Simulations of a Large-Scale Borehole Leakage Experiment - Tim Klose; M. Carme Chaparro; Frank Schilling; Christoph Butscher; Steffen Klumbach; Philipp Blum (Transport in Porous Media, 2021)
Borehole leakage is a common and complex issue. Understanding the fluid flow characteristics of a cemented area inside a borehole is crucial to monitor and quantify the wellbore integrity as well as to find solutions to minimise existing leakages. In order to improve our understanding of the flow behaviour of cemented boreholes, we investigated experimental data of a large-scale borehole leakage tests by means of numerical modelling using three different conceptual models. The experiment was performed with an autoclave system consisting of two vessels bridged by a cement-filled casing. After a partial bleed-off at the well-head, a sustained casing pressure was observed due to fluid flow through the cement–steel composite. The aim of our simulations is to investigate and quantify the permeability of the cement–steel composite. From our model results, we conclude that the flow occurred along a preferential flow path at the cement–steel interface. Thus, the inner part of the cement core was impermeable during the duration of the experiment. The preferential flow path can be described as a highly permeable and highly porous area with an aperture of about $$5\,\upmu m$$ 5 μ m and a permeability of $$3 · 10^{-12}\,m^{2}$$ 3 · 10 - 12 m 2 (3 Darcy). It follows that the fluid flow characteristics of a cemented area inside a borehole cannot be described using one permeability value for the entire cement–steel composite. Furthermore, it can be concluded that the quality of the cement and the filling process regarding the cement–steel interface is crucial to minimize possible well leakages.

Mechanical and kinetic properties of β-cardiac/slow skeletal muscle myosin - Bernhard Brenner; Nils Hahn; Eva Hanke; Faramarz Matinmehr; Tim Scholz; Walter Steffen; Theresia Kraft (Journal of Muscle Research and Cell Motility, 2012)

Consumption of meat and fish and risk of lung cancer: results from the European Prospective Investigation into Cancer and Nutrition - Jakob Linseisen; Sabine Rohrmann; Bas Bueno-de-Mesquita; Frederike L. Büchner; Hendriek C. Boshuizen; Antonio Agudo; Inger Torhild Gram; Christina C. Dahm; Kim Overvad; Rikke Egeberg; Anne Tjønneland; Heiner Boeing; et al. (Cancer Causes & Control, 2011)

The clinical value of neutrophil extracellular traps - Tim Lögters; Stefan Margraf; Jens Altrichter; Jindrich Cinatl; Steffen Mitzner; Joachim Windolf; Martin Scholz (Medical Microbiology and Immunology, 2009)

Sex recognition in brown skuas: do acoustic signals matter? - Tim Janicke; Markus S. Ritz; Steffen Hahn; Hans-Ulrich Peter (Journal of Ornithology, 2007)

Hybridisation between South polar skua (Catharacta maccormicki) and Brown skua (C. antarctica lonnbergi) in the Antarctic Peninsula region - Markus S. Ritz; Steffen Hahn; Tim Janicke; Hans-Ulrich Peter (Polar Biology, 2006)